Précis of Knowing What Things Are: An Inquiry Based-Approach - ANDRÉ J. ABATH (Manuscrito)
Abstract This book symposium comprises a précis of André J. Abath’s book Knowing What Things Are: An Inquiry-Based Approach (Springer, 2022) together with five critical commentaries on different aspects of the book-written by Veronica Campos, Guilherme Araújo Cardoso, Giulia Felappi, Ernesto Perini-Santos and Leonardo de Mello Ribeiro-, and the author’s replies.